Pengaruh Pemberian Kartu Pengingat Terhadap Kepatuhan Senam Prolanis Pada Pasien Lansia - Ike Prafita Sari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Hypertension and Diabetes Mellitus (DM) are common degenerative diseases in the elderly and are closely related, where DM sufferers are at higher risk of developing hypertension. This condition can increase the risk of serious complications such as kidney failure and cardiovascular disease. Management includes a healthy lifestyle (diet, exercise), regular monitoring, and medication as recommended by a doctor. This study aims to determine the Effect of Providing Reminder Cards on Prolanis Exercise Compliance in Elderly Patients in the Mojokerto Community Health Center Work Area. This type of research uses quasi-experimental research with a post-test only control group design. A sample of 68 elderly people who meet the inclusion criteria and the sampling technique used is purposive sampling. In this study, 2 instruments were used, namely reminder cards and MMAS-8 questionnaires and the data test used the Mann Whitney Test. The results of this study showed that in the control group that was not given reminder cards, the majority of respondents were non-compliant with treatment, as many as 22 respondents (64.7%). In the experimental group that was given reminder cards, the results showed that almost all of them were compliant, as many as 27 respondents (79.4%). The results of the Mann Whitney Test showed Asymp. Sig 0.000 ? ? (0.05) which means there is an effect of giving reminder cards on compliance with Prolanis exercise in elderly patients in the Mojokerto Community Health Center Work Area. Prolanis exercise is effective in stabilizing blood pressure and blood sugar levels, because physical activity increases insulin sensitivity and helps maintain the balance of the body's systems, thereby improving the quality of life for those with chronic diseases. It is hoped that to increase compliance with Prolanis gymnastics, Community Health Centers and other health facilities can provide reminder cards